Utilization of Industrial By-Products for Development of Controlled Low Strength Materials (CLSM) - Aggarwal, Jaideep (My University, 2024)
A controlled low strength material (CLSM) is a self-compacting flowable material using a small quantity of binder, fine aggregate and water, and are primarily employed as backfill. The specified upper limit of 28-day compressive strength for CLSM is 8.30 MPa and for future excavatability as 2.10 MPa. The low strength requirements of CLSMs make them suitable to allow utilization of low-quality industrial by-products as constituents as substitutes for conventional materials. The present study envisaged the development of sustainable CLSM suitable for practical applications, by utilization of industrial and agro by-products cement kiln dust (CKD), spent foundry sand (SFS) and unprocessed rice husk ash (RHA). For the above purpose, engineering properties of the CLSM mixes in the fresh and hardened states were evaluated. In order to ensure environmental safety for using the CLSM as backfill, these mixes were also examined in terms of their leachate toxicity. The study has been divided into three groups based on the by-products used. In Group-1, spent foundry sand completely substituted the conventional fine aggregates, while cement kiln dust replaced cement at 0%, 25%, 50%, 75% and 100% levels to form five mixes. The binder to aggregate ratio was 1:10 and water content was worked out for the flowability of around 250 mm. Addition of cement kiln dust increased flow, delayed setting time and reduced the compressive strength. The findings also indicated that spent foundry sand with 100% cement kiln dust could be successfully utilized to prepare excavatable, eco-friendly and sustainable CLSM with bearing resistance equivalent to well compacted sands, suitable for general purpose backfill. The mix with 75% cement kiln dust proved most suited from most of the aspects of a practical CLSM. In Group-2, rice husk ash was used as fine aggregate and five CLSM mixes with cement kiln dust (CKD) replacing cement like in Group-1 were studied. The binder to aggregate ratio was 1:3 and water content was worked out for the flowability of 200-250 mm. The addition of cement kiln dust increased flowability, bleeding, setting time and reduced compressive strength. The mixes with 75-100 % CKD could not attain the desired stiffness level of final setting time for a penetration resistance of 2.76 MPa. With respect to unconfined compressive strength, all the Group-2 mixes were manually excavatable and suited general backfill applications like voids, abandoned underground structures. However, the CLSM mix with 50 % CKD was best suited with respect to practical requirements of reasonable setting time alongside strength. In Group-3, proposed CLSM mixes comprised of spent foundry sand and unprocessed rice husk ash in 50:50 ratio (w/w) as fine aggregate. Five mixes with CKD and cement similar to Group-1 and Group-2 were formulated. The binder to aggregate ratio was 1:3 and a target flowability of around 200 mm was achieved. The addition of CKD resulted in a marginally higher water demand for 0-75% CKD followed by a lower demand at 100 % CKD. Further addition of CKD also delayed setting and reduced the compressive strength. The results presented the possibility of development of an environmentally safe, excavatable CLSM entirely by use of spent foundry sand, rice husk ash and cement kiln dust. The mix with 75% CKD met almost all desirable practical requirements of CLSM. Heavy metal concentrations in the leachate of prepared CLSM mixes comprising all the proposed by-products were also within the regulatory levels. Therefore, use of the above by-products in the development of CLSMs was environmentally safe from the leachate toxicity aspect. Ecological analysis of all the group CLSM mixes also showed diminished embodied energy and embodied carbon by use of by-products. Therefore, it was ecological to incorporate by-products in CLSM. For maximum benefit, the proposed application near the by-product’s source shall minimize transportation energy in addition to above ecological advantage. CLSM made by using by-products CKD, SFS and RHA can prove to be an innovative sustainable construction material facilitating valorization of agro-based and industrial by-products along with providing an effective infrastructural solution for their large-scale disposal.
Keywords: By-product; SFS; CKD; RHA; CLSM; Backfill; Sustainability; Toxicity